IMPACT OF NURSE-LED HIV/AIDS CARE AND TREATMENT PROGRAMS ON PATIENT OUTCOMES - ⁠ Mohammed Ali M Alhamdan, Eid Mutair Smayan Albnagi, Sajedah Fayed Alenazi, Abdulmohsen M Alsaeed, Mubarak Saad Mubarak Aldawsari, Jawharah Abdulrahman Bin Muaddi, Malak Mohammed Aljohani, Khalid Aali Alghamdi, ,; Nuorh Abduall Aldowai, Apdullah Saad Al Oweis, Hasnaa Falahalsady, Sara Dhahawi Awad Alruwaili, Wafa Saad Alharthi, Mei Abrahim Al Dosary, (Chelonian Research Foundation, 2022)
Home-based care is used in several nations as a means to enhance quality of life and reduce hospitalization, especially in situations when public health facilities are overwhelmed. The goals of home-based care for HIV/AIDS may include medical treatment, administration of antiretroviral therapy, and provision of psychological assistance. This evaluation evaluates the impact of home-based nursing on the incidence of illness in individuals affected by HIV/AIDS. The studies included in this study include both HIV positive adults and children, without any consideration for gender or location, and all of them were conducted using a randomized controlled design. A comparison was made between home-based care administered by competent nurses and therapy delivered in hospitals or health facilities. The electronic databases AIDSearch, CINAHL, Cochrane Register of Controlled Trials, EMBASE, MEDLINE, and PsycINFO/LIT were searched. Nurse-led home-based care resulted in an increase in reported adherence to antiretroviral medicines, however, it did not have an impact on viral load. Psychiatric nurse assistance enhanced mental health and alleviated depressed symptoms in individuals with preexisting mental health issues. Psychological assistance provided at home had a significant effect in reducing HIV stigma, concern, and physical impairment. In some instances, it even helped alleviate depressed symptoms. Home-based programs guided by nurses have the potential to enhance adherence to antiretroviral medication and promote better mental health. Additional comprehensive research is required to thoroughly investigate the enhancement of medical treatment for HIV, particularly in regards to the screening and management of opportunistic infections and co-morbidities. Keywords: HIV/AIDS, nurse staff, nurse intervention, review, treatment program, Home-based care.